Determinants of Fever in Acute Stroke Patients - Karn, Ragesh; Tharu, Biswaraj; Basnet, Sijan; Subedi, Kamal (Nepal Journal of Neuroscience, 2016)
The aim of this study was to determine the frequency and origin of fever in patients admitted with acute stroke and the characteristics associated with the development of fever.This was a cross sectional observational study involving 151 patients admitted with acute stroke. The various attributes associated with the development of fever were documented and their characteristics were analyzed.Fever was noted in 21.2% of 151 patients; 11.9% had a documented infection and 9.3% had no documented infection. Older age was associated with the presence of fever (P = 0.009). The development of fever was associated with haemorrhage rather than ischemic infarct (P = 0.0001), presence of mass effect (P =0.03), and larger size of ischaemic infarct and haemorrhage (P = 0.002 and 0.0001, respectively). Patients with fever had lower scores on admission on the Glasgow Coma Scale (GCS) (P = 0.009) and higher score on the National Institute of Health Stroke Scale (NIHSS) (P = 0.0001). The development of fever was associated with prior use of an invasive technique (P =0.0001), particularly urinary catheterization and endotracheal intubation (P = 0.0001 and 0.0001). In multivariate analysis, age, NIHSS and endotracheal intubation were found to be significantly associated with fever (P = 0.018, P = 0.001 and P = 0.0001, respectively). Patients with fever without documented infection had an earlier onset than those with infection (P = 0.012).Fever in acute stroke patients is associated with older age, severity of stroke and the use of invasive techniques. Urinary tract and respiratory infections are the most common infections. Fever starts earlier where a focus of infection is not identified.Nepal Journal of Neuroscience 12:20-25, 2015